What are reasons for the large gender differences in the lethality of suicidal acts? An epidemiological analysis in four european countries - Mergl, Roland (2022)
The research leading to these results has received funding from the European Commission (ec.europa.eu) within the Seventh Framework Programme under grant agreement N° 223138. The following authors received the funding: NK KH A. Székely MT RG SQ EA CC MM AV CVA DMcD MS A. Schmidtke AG JC UH. The authors also acknowledge support from the German Research Foundation (DFG) and Universität Leipzig within the program of Open Access Publishing. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.